Techniques for Continuous Irrigation of Septic Joints of the Hand. Issue 3 (September 2019) - Chung, Sze-Ryn; Kang, Yong Chiang; McGrouther, Duncan Angus
Abstract : Septic arthritis of the small joints of the hand usually occurs secondary to bacterial inoculation through penetrating injury to the joint, or direct spread of infection from paronychia, felon, or pyogenic flexor tenosynovitis. Surgical treatment involves drainage and irrigation and may involve debridement if there is an open wound. We describe a method of continuous irrigation of septic joints of the hand postoperatively in the ward setting using an intravenous cannula placed within the joint and connected to an intravenous giving set with delivery of physiological fluid using a pump driver. Modifications of the technique are described for distal interphalangeal, proximal interphalangeal, and metacarpophalangeal joints and illustrated in each joint by 3 case studies. In addition to the irrigation, intravenous antibiotics were administered. All patients healed well with a full return of joint motion, no radiologic change, and a mean QuickDASH score of 4.8 at a mean follow-up duration of 3.6 months. This is a safe and simple technique that can be performed in patients with suspected or confirmed septic arthritis and carries minimal morbidity.